2005
DOI: 10.1007/s10209-005-0116-3
|View full text |Cite
|
Sign up to set email alerts
|

Robotic assistants in therapy and education of children with autism: can a small humanoid robot help encourage social interaction skills?

Abstract: This article presents a longitudinal study with four children with autism who were exposed to a humanoid robot over a period of several months. The longitudinal approach allowed the children time to explore the space of robot-human, as well as human-human interaction. Based on the video material documenting the interactions, a quantitative as well as qualitative analysis was conducted. The quantitative analysis showed an increase in duration of pre-defined behaviours towards the later trials. A qualitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
308
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 573 publications
(351 citation statements)
references
References 23 publications
7
308
1
12
Order By: Relevance
“…This pattern could indicate a different apperception of virtual faces. Virtual characters may be inherently less intimidating than real faces due to their game-like qualities and the intrinsic unreality of the virtual worlds they inhabit (Marsella et al, 2003;Robins et al, 2005). The fact that virtual faces may be perceived as less intimidating by patients may entail an advantage for therapy programs: it facilitates learning of social skills under relatively lower stimulusinduced anxiety.…”
Section: Psychopathologymentioning
confidence: 99%
“…This pattern could indicate a different apperception of virtual faces. Virtual characters may be inherently less intimidating than real faces due to their game-like qualities and the intrinsic unreality of the virtual worlds they inhabit (Marsella et al, 2003;Robins et al, 2005). The fact that virtual faces may be perceived as less intimidating by patients may entail an advantage for therapy programs: it facilitates learning of social skills under relatively lower stimulusinduced anxiety.…”
Section: Psychopathologymentioning
confidence: 99%
“…Outro setor em que a robótica tem sido utilizada com sucesso é a Medicina. Neste setor, os robôs móveis têm sido aplicados com êxito em exercícios de reabilitação (REINKENSMEYER et al, 2001;URIBE-QUEVEDO, 2011), para a interação com crianças autistas (ROBINS, B. et al, 2005), inclusão social de crianças com deficiências motoras severas (VALADÃO et al, 2011), e robôs de companhia para pessoas com deficiência (REMAZEILLES et al, 2008). …”
Section: Justificativa E Motivaçãounclassified
“…Nesta área, o uso de robôs sociais assistivos é relevante, visto que podem auxiliar tanto no tratamento da disfunção, quanto na inclusão social do sujeito. De fato, estes robôs têm sido aplicados com êxito em exercícios de reabilitação (REINKENSMEYER et al, 2001; URIBE-QUEVEDO, 2011), para a interação com crianças com Transtorno do Espectro Autista (TEA) (COECKELBERGH et al, 2015;DAUTENHAHN;BILLARD, 2002;DUQUETTE et al, 2007;IACONO et al, 2011;KIM, Elizabeth et al, 2012;KIM, Elizabeth S. et al, 2013;CLAVET, 2001;ROBINS, B. et al, 2005;ROBINS, Ben et al, 2010;WERRY;DAUTENHAHN, 1999), inclusão social para crianças com deficiências motoras severas (VALADÃO et al, 2011), e robôs de companhia para auxiliar pessoas com deficiência (REMAZEILLES et al, 2008). Consequentemente, a pertinência dessa área e o sucesso de iniciativas correlatas subsidiaram o desenvolvimento de um estudo de caso sobre o uso de robótica social assistiva como ferramenta auxiliar para educação especial de crianças com TEA, para o qual a organização da arquitetura de controle inteligente foi utilizada e avaliada.…”
Section: Deliberanteunclassified
See 1 more Smart Citation
“…For example, children with autism are known to respond to simple mobile car-like robots as well as to humanoid machines. However, pilot experiments have suggested that humanoid robots may be overwhelming and intimidating, while others have shown therapeutic benefit [105,108]. Biomimetic, and more specifically, anthropomorphic form allows human-like gestures and direct imitation movements, while non-biomimetic form preserves the appeal of computers and mechanical objects.…”
Section: Embodimentmentioning
confidence: 99%